Representations of Couple Relationships in Chilean Film Comedy [Las Representaciones de Las Relaciones de Pareja en la Comedia Cinematográfica Chilena] - Valenzuela-Somogyi, M (Universidad de Talca, 2022)
The results of a study on the representation of couple relationships in eight Chilean films of the cinematographic comedy genre, shown between 1999 and 2020, are presented based on an inductive qualitative film analysis methodology. It is argued that the reading on couple relationships is structured from an interpretation of gender transformations, in which the figure of the woman is constructed from a demand for horizontality and recognition that implies that in the man is developed an identity crisis associated with the masculinity referents of the traditional conjugal family model. The tension in couple relationships is caused by the entry of women into public world, and the frustration in the exercise of sexuality from a claim for sexual enjoyment that must be answered. What allows the permanence of the couple relationship is the feeling of love, revealing a discourse that places family unity and individual self-realization through the couple as the center. © 2022 Universidad de Talca. All rights reserved.